Addition of Euchema cottoni Carrageen to the Characteristics of Kurisi Fish (Nemipterus nematophorus) Pempek - TRI ADI WIBOWO; DESY SASRI UNTARI; ARLIN WIJAYANTI (JURNAL LEMURU, 2026)
Gel-based diversified fish products such as pempek generally have a chewy texture due to the formation of a fish protein gel matrix that is reinforced by tapioca starch during mixing and cooking processes such as boiling. However, in their processing, errors in stages commonly occur that can result in a final product that is not chewy. Therefore, a gelling agent is needed to maintain its chewy texture, such as carrageenan. Threadfin bream fish (Nemipterus nematophorus) is a type of fish with white flesh that is high in protein, but its potential as a raw material for diversified fish products has not been fully utilized. This study aims to examine the effect of adding carrageenan extracted from Eucheuma cottonii seaweed on the sensory characteristics of pempek from Threadfin bream fish, including appearance, odor, taste, and texture. The method used was a completely randomized design (CRD) non-factorial with four carrageenan addition treatments (0%, 2%, 4%, and 6%) and three replications. The characteristic tests included appearance, aroma, taste, and texture. The results showed that the addition of carrageenan had a significant effect on the appearance, aroma, and taste of pempek (P<0.05), but did not significantly affect the texture (P>0.05). The best treatment was obtained with the addition of 2% carrageenan. The highest carrageenan concentration (6%) had the lowest value, as it produced a darker product, a slightly rancid aroma, and a firmer texture. Overall, the addition of 2% Eucheuma cottonii carrageenan improved the sensory quality of pempek from Threadfin bream fish